A negative electrode active material, a preparation method thereof, a negative electrode sheet, a battery, a battery pack, and an electric device
Patent Information
- Application Number
- CN202510499286.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2026-10-23
AI Technical Summary
但是形成的纳米硅颗粒尺寸不均匀,纳米硅比表面积较高,表面活性强容易被氧化
[0037]本发明提供的负极活性材料通过将硅设计为纳米尺寸,可以显著减少体积变化对材料结构的影响,提高循环寿命,此外,纳米尺寸的硅提供了更大的比表面积,有利于锂离子的快速嵌入和脱出;而且由于硅碳材料具有包含碳纳米笼的碳骨架,且纳米硅设置在纳米笼表面,这样不仅提供了良好的电子传导路径,有抑制解纳米硅材料的团聚,还能够有效释放在充放电过程中体积膨胀带来的应力,提高负极活性材料的循环稳定性。同时,包覆层能有效地保护纳米硅,防止其与电解液直接接触,从而减少副反应的发生。因此,在特定组成结构的多方协同作用下,使负极活性材料具有良好的电化学性能和稳定性。
Smart Images

Figure CN122968280A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, and more particularly to a negative electrode active material and its preparation method, a negative electrode sheet, a battery, a battery pack, and electrical equipment. Background Technology
[0002] Graphite, as the main negative electrode active material for power batteries, can no longer meet the market's increasingly high energy density requirements. Silicon materials, on the other hand, have advantages such as high theoretical capacity, low lithium intercalation platform, and abundant resources, and are expected to become the next generation of negative electrode active materials to replace graphite.
[0003] However, silicon undergoes significant volume expansion during lithium intercalation, leading to structural pulverization and instability at the solid electrolyte intercalation (SEI) interface, ultimately resulting in reduced lithium intercalation capacity. To mitigate the size effect of lithium intercalation, silicon is typically nano-sized to reduce its size and alleviate the expansion. However, the resulting nano-silicon particles are non-uniform in size, have a high specific surface area, and are highly reactive, making them prone to oxidation.
[0004] Therefore, there is an urgent need to explore nano-silicon-carbon materials with higher stability to expand the application of anode active materials. Summary of the Invention
[0005] This invention provides a negative electrode active material with a core-shell structure. Under the synergistic effect of silicon-carbon material with a specific composition and coating layer, it is not easily broken and has a low expansion rate, thus making the structure of the negative electrode active material stable.
[0006] The present invention also provides a method for preparing a negative electrode active material, which is simple to operate and can prepare the above-mentioned negative electrode active material.
[0007] The present invention also provides a negative electrode sheet comprising the above-mentioned negative electrode active material, thus exhibiting excellent electrochemical performance and cycle stability.
[0008] The present invention also provides a battery comprising the above-mentioned negative electrode sheet, which has excellent electrochemical performance and stability.
[0009] The present invention also provides a battery pack, the battery comprising the above-described battery, having excellent electrochemical performance and stability.
[0010] The present invention also provides an electrical device comprising the aforementioned battery, which has excellent performance.
[0011] The present invention provides a negative electrode active material, comprising a silicon-carbon material and a coating layer disposed on at least a portion of the surface of the silicon-carbon material;
[0012] The silicon-carbon material includes a carbon skeleton, which comprises several carbon nanocages, and the surface of the carbon nanocages is provided with nano-silicon.
[0013] In the negative electrode active material described above, the pore size of the carbon framework is 0.5 nm to 10 nm;
[0014] And / or, the average size of the carbon nanocages is 8 nm to 30 nm;
[0015] And / or, the particle size of the nano-silicon is no greater than 1 nm.
[0016] In the negative electrode active material described above, the degree of graphitization of the carbon skeleton is 1.6 to 4;
[0017] And / or, the degree of graphitization of the silicon-carbon material is 1.0 to 2.8.
[0018] In the negative electrode active material described above, the carbon skeleton is spherical or near-spherical;
[0019] And / or, the specific surface area of the carbon skeleton is 400–3000 m². 2 / g;
[0020] And / or, the carbon nanocage is spherical or near-spherical;
[0021] And / or, the inner surface of the carbon nanocage is provided with the nano-silicon;
[0022] And / or, the nano-silicon has an amorphous structure.
[0023] The negative electrode active material as described above, wherein the coating layer comprises at least one of carbon, metal oxide, phosphate compound, and aluminate compound;
[0024] And / or, the thickness of the coating layer is 5nm-30nm.
[0025] The negative electrode active material described above has a particle size D50 of 5 μm to 15 μm.
[0026] As described above, in the negative electrode active material, the mass percentage of the nano-silicon is 30%-60%, and the mass percentage of the coating layer is 2%-10%, based on the mass of the negative electrode active material.
[0027] In another aspect, the present invention provides a method for preparing the negative electrode active material as described above, comprising the following steps:
[0028] 1) The carbon framework precursor was treated at a temperature of 1200℃~3000℃ for 6-14h to obtain a carbon framework including carbon nanocages.
[0029] 2) The carbon framework is deposited using a silicon source to obtain the silicon-carbon material;
[0030] 3) A coating layer is formed on the surface of the silicon-carbon material to obtain the negative electrode active material.
[0031] In the preparation method described above, the carbon framework precursor is mesophase carbon microspheres.
[0032] In the preparation method described above, the temperature of the vapor deposition is 400–600°C, and the time is 4–8 hours.
[0033] In another aspect, the present invention provides a negative electrode sheet, comprising the negative electrode active material as described above or the negative electrode active material prepared by the preparation method described above.
[0034] In another aspect, the present invention provides a battery comprising the negative electrode sheet as described above.
[0035] In another aspect, the present invention provides a battery pack comprising at least two batteries as described above.
[0036] In another aspect, the present invention provides an electrical device comprising a battery or battery pack as described above.
[0037] The negative electrode active material provided by this invention, by designing silicon to the nanoscale, can significantly reduce the impact of volume changes on the material structure and improve cycle life. Furthermore, the nanoscale silicon provides a larger specific surface area, which is beneficial for the rapid insertion and extraction of lithium ions. Moreover, since silicon-carbon materials have a carbon framework containing carbon nanocages, and the nano-silicon is disposed on the surface of the nanocages, this not only provides a good electron conduction pathway and inhibits the aggregation of nano-silicon materials, but also effectively releases the stress caused by volume expansion during charge and discharge, improving the cycle stability of the negative electrode active material. Simultaneously, the coating layer effectively protects the nano-silicon, preventing it from directly contacting the electrolyte, thereby reducing the occurrence of side reactions. Therefore, through the synergistic effect of multiple factors in the specific composition and structure, the negative electrode active material exhibits excellent electrochemical performance and stability. Attached Figure Description
[0038] Figure 1 This is a schematic diagram of the carbon skeleton provided in Embodiment 1 of the present invention;
[0039] Figure 2 This is a scanning electron microscope image of the carbon framework before the deposition of nano-silicon provided in Example 2 of the present invention. Detailed Implementation
[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0041] Typically, silicon in anode active materials is nano-sized to reduce its size, which can effectively alleviate lithium intercalation expansion. However, the current preparation process for nano-silicon materials is complex, resulting in non-uniform silicon particle sizes. The resulting nano-silicon particles are highly active and easily oxidized, which significantly affects their stability as anode active materials. Although surface passivation can mitigate this, the effect is not ideal.
[0042] Improving the stability of nano-silicon materials, thereby enhancing the performance of anode active materials, has become a research direction for researchers.
[0043] The present invention provides a negative electrode active material, comprising a silicon-carbon material and a coating layer disposed on at least a portion of the surface of the silicon-carbon material;
[0044] The silicon-carbon material includes a carbon skeleton, which comprises several carbon nanocages, and the surface of the carbon nanocages is provided with nano-silicon.
[0045] The negative electrode active material provided by this invention has a core-shell structure, wherein silicon-carbon material is the core and the coating layer is the outer shell.
[0046] In detail, the coating layer covers part or all of the surface of the silicon-carbon material.
[0047] Among them, carbon nanocages are cage-like structures with cavities formed by the curling and surrounding of carbon layers. Because the average size of carbon nanocages is on the nanometer scale, they are extremely prone to aggregation. When several carbon nanocages aggregate, they can form a framework structure, namely the carbon framework mentioned above. See the structural diagram. Figure 1 .
[0048] In some embodiments, the framework may also be a carbon matrix, with several carbon nanocages aggregated on the carbon matrix. The carbon matrix may be at least one of soft carbon, hard carbon, or porous carbon.
[0049] In some embodiments, the surface of the carbon nanocage can refer to either the outer surface of the carbon nanocage or the inner surface of the cage pores extending into the interior.
[0050] In this invention, nano-silicon refers to silicon nanoparticles with an average particle size of no more than 1 μm. Measurement can be performed using methods commonly used in the art, such as transmission electron microscopy.
[0051] The negative electrode active material provided by this invention exhibits both the volume stability of nano-silicon and good stability. By designing silicon to a nanoscale, the impact of volume changes on the material structure can be significantly reduced, improving cycle life. Furthermore, nano-sized silicon provides a larger specific surface area, which is beneficial for the rapid insertion and extraction of lithium ions. Moreover, since silicon-carbon materials have a carbon framework containing carbon nanocages, and the nano-silicon is disposed on the surface of the nanocages, this not only provides a good electron conduction pathway and inhibits the aggregation of nano-silicon materials, but also effectively releases the stress caused by volume expansion during charge and discharge, improving the cycle stability of the negative electrode active material. Simultaneously, the coating layer effectively protects the nano-silicon, preventing it from directly contacting the electrolyte, thereby reducing the occurrence of side reactions. Therefore, through the synergistic effect of multiple factors in the specific composition and structure, the negative electrode active material possesses excellent electrochemical performance and stability.
[0052] In one specific embodiment, the pore size of the carbon skeleton is 0.5 nm to 10 nm.
[0053] The pore size of the carbon framework is mainly provided by the cavity of the carbon nanocage, which has an important influence on the metal ion transport rate, the deposition distribution of nano-silicon, and the volume expansion buffer. A suitable pore size helps to balance the metal ion transport rate and structural stability, and can also enable the nano-silicon to be uniformly distributed, providing sufficient space buffer for the volume expansion of nano-silicon, thereby improving cycle stability.
[0054] The pore size of the carbon framework refers to the average pore size, which can be measured using methods commonly used in the field, such as transmission electron microscopy. For example, when a single carbon nanocage is identified from a TEM image, the maximum inner diameter of that single carbon nanocage is its pore size. The average pore size of multiple carbon nanocages is the pore size of the carbon framework. The number of carbon nanocages is unlimited; the more, the better.
[0055] For example, the pore size of the carbon framework includes, but is not limited to, a range of 0.5 nm, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, or any combination thereof.
[0056] In one specific embodiment, the carbon nanocage has an average size of 8 nm to 30 nm.
[0057] The average size of carbon nanocages within the above range can provide suitable surface monolithic silicon nanoparticles, enabling them to be dispersed uniformly, effectively relieving expansion stress, and increasing the electrochemical performance of the negative electrode active material.
[0058] The average size of the carbon nanocages can be measured using methods common in the field, such as transmission electron microscopy. For example, by identifying a single carbon nanocage from a TEM image and measuring its maximum outer diameter, the size of a single carbon nanocage is obtained. The average size of multiple carbon nanocages is the average size of the carbon nanocage. The number of carbon nanocages is unlimited; the more, the better.
[0059] For example, the average size of carbon nanocages includes, but is not limited to, a range of 8 nm, 10 nm, 12 nm, 15 nm, 17 nm, 19 nm, 21 nm, 23 nm, 25 nm, 27 nm, 30 nm, or any two of these.
[0060] In one specific embodiment, the particle size of the nano-silicon is no greater than 1 nm. In this embodiment, the nano-silicon can further reduce the impact of volume change on the material structure, thereby improving the cycle stability of the negative electrode active material and increasing the cycle life of the battery.
[0061] In one specific embodiment, the degree of graphitization of the carbon skeleton is 1.6 to 4.
[0062] The degree of graphitization in this invention refers to I G / I D The numerical value can be measured by Raman spectroscopy, where I G The intensity of the G peak in the Raman spectrum is related to the ordered carbon structure, while the I peak... D The intensity of the D peak in a Raman spectrum is related to defects or disordered structures in the material.
[0063] In detail, the degree of graphitization of the carbon skeleton includes, but is not limited to, a range of 1.6, 2, 2.5, 3, 3.5, 4, or any two of these.
[0064] When the degree of graphitization of the carbon skeleton is within the above range, the highly ordered carbon skeleton is beneficial to ion and electron transport and improves kinetics; at the same time, it increases particle strength and reduces particle breakage during the preparation of the negative electrode.
[0065] In one specific embodiment, the graphitization degree of the silicon-carbon material is 1.0 to 2.8.
[0066] When the graphitization degree of silicon-carbon materials is within the above range, the transport of ions and electrons can be further guaranteed, while the particle strength is improved and the breakage of particles during the preparation of the negative electrode sheet is reduced.
[0067] In detail, the degree of graphitization of silicon-carbon materials includes, but is not limited to, a range of 1.0, 1.2, 1.5, 1.6, 2.0, 2.2, 2.5, 2.8, or any two of these ranges.
[0068] In one specific embodiment, the carbon skeleton is spherical or near-spherical, wherein the spherical or near-spherical carbon skeleton helps to further enhance the strength of the negative electrode active material, thereby further alleviating the stress caused by the volume expansion of nano-silicon during charging and discharging, and improving the cycle stability of the negative electrode active material.
[0069] The specific surface area of the carbon skeleton also has a certain impact on the electrochemical performance and stability of the negative electrode active material.
[0070] In one specific embodiment, the specific surface area of the carbon skeleton is 400–3000 m². 2 / g.
[0071] In detail, the specific surface area of the carbon skeleton includes, but is not limited to, 400 m². 2 / g、500m 2 / g, 1000m 2 / g, 1500m 2 / g、2000m 2 / g、2500m 2 / g、3000m 2 / g or a range consisting of any two of them.
[0072] When the specific surface area of the carbon skeleton is within the above range, a better conductive network can be formed, which helps the uniform distribution of nano-silicon on the carbon skeleton, prevents the agglomeration of nano-silicon, gives full play to the role of nano-silicon, provides sufficient space for the volume expansion of nano-silicon, and thus improves the stability of the negative electrode active material.
[0073] In one specific embodiment, the carbon nanocage is spherical or near-spherical. The spherical or near-spherical carbon nanocage is beneficial for dispersing the stress during silicon expansion. Furthermore, when the spherical or near-spherical carbon nanocage aggregates, it helps to increase the strength and structural density of the framework, further enhancing the strength of the negative electrode active material and improving the cycle stability of the negative electrode active material.
[0074] In one specific embodiment, the inner surface of the carbon nanocage is provided with the nano-silicon. The nano-silicon, disposed on the inner surface of the carbon nanocage, can better alleviate the stress caused by the volume expansion of the nano-silicon during charging and discharging, thereby further ensuring the cycle stability of the negative electrode active material.
[0075] In one specific embodiment, the nano-silicon has an amorphous structure. The amorphous structure of nano-silicon can be determined by XRD. Typically, amorphous silicon does not show obvious diffraction peaks in XRD patterns, but rather exhibits broad and diffuse scattering peaks.
[0076] In one specific embodiment, the coating layer includes at least one of carbon, metal oxides, phosphate compounds, and aluminate compounds.
[0077] The coating material described above can effectively protect silicon-carbon materials while improving their conductivity.
[0078] The particle size D50 also has a significant impact on the stability and conductivity of the negative electrode active material. In one specific embodiment, the particle size D50 of the negative electrode active material is 5 μm to 15 μm.
[0079] In this context, the particle size D50 of the negative electrode active material refers to the value in which 50% of the particles in the particle size distribution have a diameter smaller than this value. Common measurement methods, such as laser particle size analysis, can be used for detection.
[0080] In detail, the particle size D50 of the negative electrode active material includes, but is not limited to, a range of 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, or any combination thereof.
[0081] When the particle size D50 of the negative electrode active material is within the above range, it can provide a more suitable specific surface area, effectively buffering the volume changes caused by lithium ion insertion and extraction during charging and discharging, thus improving the stability of the negative electrode active material. On the other hand, it helps to shorten the diffusion path of ions and electrons, increase the ion transport rate, and improve the conductivity of the negative electrode active material.
[0082] Since the negative electrode active material contains multiple components, the appropriate mass ratio between the components helps to better exert the synergistic effect of each part and further improve the material performance.
[0083] In one specific embodiment, based on the mass of the negative electrode active material, the mass percentage of nano-silicon is 30%-60%, and the mass percentage of the coating layer is 2%-10%.
[0084] It is understandable that, apart from the nano-silicon and the coating layer, the remainder is a carbon skeleton. In detail, based on the mass of the negative electrode active material, the mass percentage of nano-silicon includes, but is not limited to, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or any combination thereof.
[0085] Based on the mass of the negative electrode active material, the mass percentage of the coating layer includes, but is not limited to, 2%, 4%, 6%, 8%, 10%, or any combination thereof.
[0086] For example, the mass of each component of the negative electrode active material can be tested by thermogravimetric analysis (TGA).
[0087] It is understandable that the mass content ratio of various components in the final negative electrode active material can be controlled by controlling the amount of each component added during the preparation process.
[0088] When the mass percentages of various components in the negative electrode active material are within the aforementioned range, not only can the high theoretical capacity of silicon be utilized, but the volume expansion of silicon can also be buffered, improving the stability of the negative electrode active material. Simultaneously, a suitable coating layer can form a more stable solid electrolyte interphase (SEI) film on the nano-silicon surface, reducing side reactions and improving the battery's initial coulombic efficiency and cycle stability.
[0089] When the composition and mass ratio of the coating layer are adjusted, the thickness of the coating layer will be affected. In one specific embodiment, the thickness of the coating layer is 5nm-100nm.
[0090] The thickness of the coating layer in this invention refers to the average thickness. Common methods can be used to measure the thickness of the carbon coating layer, such as transmission electron microscopy.
[0091] In detail, the thickness of the coating layer includes, but is not limited to, a range of 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 100 nm, or any two of these.
[0092] When the coating thickness is within the aforementioned range, a moderate coating thickness can effectively buffer the stress caused by volume changes in silicon during charging and discharging, reduce the pulverization of nano-silicon, and improve cycle stability. Simultaneously, it can form a stable interface between the electrolyte and silicon-carbon materials, reducing side reactions and extending battery life. Furthermore, a coating thickness of the aforementioned amount provides sufficient protection without significantly hindering lithium-ion transport.
[0093] In another aspect, the present invention provides a method for preparing the negative electrode active material as described above, comprising the following steps:
[0094] 1) The carbon framework precursor was treated at a temperature of 1200℃~3000℃ for 6-14h to obtain a carbon framework including carbon nanocages.
[0095] 2) The carbon framework is deposited using a silicon source to obtain the silicon-carbon material;
[0096] 3) A coating layer is formed on the surface of the silicon-carbon material to obtain the negative electrode active material.
[0097] In detail, in step 1), the carbon skeleton precursor is treated at a high temperature of 1200℃~2800℃ for 6-12 hours, which promotes the rearrangement of carbon atoms, resulting in recombination and graphitization. This recombination changes the pore structure of the carbon skeleton precursor, forming a carbon skeleton.
[0098] Understandably, carbon skeleton precursors readily react with oxygen at high temperatures, so heat treatment is usually performed in an inert atmosphere to prevent oxidation and material loss, for example, in an argon atmosphere.
[0099] In step 2), a silicon source is used to perform vapor deposition on the carbon skeleton. During the vapor deposition process, the silicon source forms silicon atoms, which are deposited on the surface of the cage pores of the carbon skeleton to form sub-nanometer-sized nano-silicon, thus obtaining a silicon-carbon material including a carbon skeleton with deposited nano-silicon.
[0100] This invention does not limit the specific type of silicon source, and can use common silicon sources in the field, such as silane, ethoxysilane, silicon chloride, etc.
[0101] In step 3), a coating layer is formed on the surface of silicon-carbon material using a coating layer precursor to obtain the negative electrode active material.
[0102] In this invention, the specific type of coating layer precursor is not limited, and common raw materials in the art can be selected. For example, in one specific embodiment, the composition of the coating layer includes carbon, and the coating layer precursor can be methane, acetylene, ethylene, etc.
[0103] Common coating methods can be used to form a coating layer on the surface of silicon-carbon materials, such as chemical vapor deposition, solution method, and physical vapor deposition.
[0104] In one specific embodiment, methane is used as a coating layer precursor, and a carbon coating layer is coated onto silicon-carbon material using a vapor deposition method. During the vapor deposition process, the CH bonds in the methane are broken, and the carbon is carbonized on the surface of the silicon-carbon material to form a carbon coating layer.
[0105] The preparation method provided by this invention is simple to operate, and the prepared negative electrode active material has excellent stability and electrochemical performance.
[0106] When depositing nano-silicon, the appropriate temperature and time can decompose commonly used silicon sources and deposit nano-silicon without causing excessive thermal damage to the structure of carbon nanocages. This helps to maintain the integrity and pore structure of carbon nanocages and ensures that nano-silicon forms a uniform coating on the surface and pores of carbon nanocages, thus giving full play to the role of nano-silicon.
[0107] In one specific embodiment, the carbon framework precursor is a mesophase carbon microsphere.
[0108] Among them, mesophase carbon microspheres are more likely to form a stable carbon framework.
[0109] In one specific embodiment, the temperature for vapor deposition is 400-600°C, and the time is 4-8 hours.
[0110] In detail, the temperature for vapor deposition includes, but is not limited to, a range of 400°C, 450°C, 500°C, 550°C, 600°C or any combination thereof, and the time includes, but is not limited to, a range of 4h, 5h, 6h, 7h, 8h or any combination thereof.
[0111] Choosing the right temperature and time during the coating process can also ensure the stability and electrochemical performance of the negative electrode active material.
[0112] In one specific embodiment, in step 3), the temperature of the coating process is 500-700°C and the time is 50-500 min.
[0113] In detail, the temperature of the coating process includes, but is not limited to, a range of 500°C, 550°C, 600°C, 650°C, 700°C or any combination thereof, and the time includes, but is not limited to, a range of 50 min, 100 min, 150 min, 200 min, 400 min, 500 min or any combination thereof.
[0114] When the temperature and time of the coating process are within the above range, not only can the coating precursor be effectively decomposed, the coating rate be increased, and a dense coating layer be formed, but the integrity of the nano-silicon can also be effectively maintained, avoiding side reactions of the nano-silicon at higher temperatures, which would affect the performance of the nano-silicon during use, thereby ensuring the conductivity and stability of the negative electrode active material.
[0115] In another aspect, the present invention provides a negative electrode sheet, comprising the negative electrode active material as described above or the negative electrode active material prepared by the preparation method described above.
[0116] Since the negative electrode sheet provided by the present invention includes the above-mentioned negative electrode active material or the negative electrode active material prepared by the above-mentioned method, the negative electrode sheet has excellent electrochemical performance and stability.
[0117] The negative electrode sheet of the present invention specifically includes a negative electrode current collector and a negative electrode active layer formed of a negative electrode active material disposed on the surface of the negative electrode current collector.
[0118] In the specific preparation of the negative electrode sheet, the negative electrode active material, conductive agent, and binder can be dispersed in an appropriate amount of deionized water and thoroughly stirred to form a uniform negative electrode slurry. The negative electrode slurry is then uniformly coated onto the negative electrode current collector, and after drying, rolling, and slitting, the negative electrode sheet is obtained. In one specific embodiment, the negative electrode active layer comprises, by weight percentage, 70-99 wt% of negative electrode active material, 0.5-15 wt% of conductive agent, and 0.5-15 wt% of binder; more specifically, it comprises 80-98 wt% of negative electrode active material, 1-10 wt% of conductive agent, and 1-10 wt% of binder.
[0119] The negative electrode current collector layer can be made of at least one of copper foil, nickel foam, and copper foam; the conductive agent can be made of at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; and the binder can be made of at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0120] In another aspect, the present invention provides a battery comprising the negative electrode sheet as described above.
[0121] It is conceivable that, in addition to the aforementioned negative electrode, the battery of the present invention also includes a positive electrode, an electrolyte, and a separator.
[0122] This invention does not strictly limit the positive electrode active material in the positive electrode sheet. Taking lithium-ion batteries as an example, it can be a positive electrode active material commonly used in lithium-ion batteries, such as at least one composite oxide of lithium with cobalt, manganese, nickel, or combinations thereof. More specifically, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate (LFP), lithium nickel manganese oxide, lithium-rich manganese-based materials, etc.
[0123] This invention does not strictly limit the choice of electrolyte. Taking lithium-ion batteries as an example, it can include one or more of the solvents commonly used in lithium-ion battery electrolytes, as well as the electrolyte lithium salts commonly used in lithium-ion electrolytes. For example, the solvent can be ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, methyl ethyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the lithium salt can be one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0124] This invention does not strictly limit the choice of separator material. Taking lithium-ion batteries as an example, it can be one of the separator materials commonly used in lithium-ion batteries, such as polypropylene separator (PP), polyethylene separator (PE), polypropylene / polyethylene double-layer composite membrane (PP / PE), polyimide electrospun separator (PI), polypropylene / polyethylene / polypropylene triple-layer composite membrane (PP / PE / PP), cellulose nonwoven separator, and separator with ceramic coating.
[0125] In battery manufacturing, the positive electrode, separator, and negative electrode are wound or stacked to obtain a bare cell, which is then packaged into a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dried battery. The battery undergoes resting, formation, and secondary sealing to complete battery manufacturing.
[0126] In another aspect, the present invention provides a battery pack comprising at least two batteries as described above.
[0127] In another aspect, the present invention provides an electrical device comprising a battery or battery pack as described above.
[0128] This invention does not limit the specific type of electrical equipment, and may include any device that requires a battery to power it, such as electric vehicles, mobile phones, smart home devices, robots, drones, e-cigarettes, and speakers.
[0129] The electrical equipment provided by the present invention includes the battery described above or the battery pack described above, and therefore has good performance.
[0130] The present invention will be further described below through specific embodiments.
[0131] Example 1
[0132] The preparation method of the negative electrode active material in this embodiment includes the following steps:
[0133] 1. Mesophase carbon microspheres (MCMB carbon microspheres) were carbonized in a high-temperature furnace filled with argon (Ar) at 2800℃ for 8 hours to obtain a carbon framework.
[0134] 2. Place 50g of carbon skeleton in a vacuum stainless steel tube furnace, introduce silane gas into the tube furnace at a flow rate of 1000ml / min, and heat treat at 500℃ for 6h. The silane undergoes thermal decomposition in the vacuum tube furnace at 500℃ to form silicon atoms, which are deposited on the pores of the carbon nanocage skeleton to form sub-nanometer silicon, thus forming a carbon skeleton with deposited nano-silicon.
[0135] 3. Place 50g of carbon skeleton with deposited nano-silicon into a tube furnace again, introduce methane gas into the tube furnace, and heat to 600℃ for 1 hour. The methane causes the CH bond to break at high temperature, and the carbon skeleton with deposited nano-silicon is further carbonized at high temperature to form a carbon coating layer, thus obtaining the negative electrode active material.
[0136] in, Figure 1 A schematic diagram of the carbon skeleton provided in Example 1, by Figure 1 It is known that when mesophase carbon microspheres are heat-treated at high temperature, highly ordered nanopores are formed inside the carbon microsphere particles, which is conducive to the deposition of nano-silicon. The highly ordered carbon skeleton is conducive to the conduction of ions and electrons.
[0137] Example 2-18
[0138] The preparation method of the negative electrode active material provided in this embodiment differs from that in Example 1, as shown in Table 1.
[0139] Comparative Example 1
[0140] The negative electrode active material provided in this comparative example uses commercial porous carbon (commercial porous carbon produced by Hunan Solide New Material Technology Co., Ltd., with a micropore (<2nm) ratio >90%) as the carbon skeleton, and the rest of the preparation process is the same as in Example 1.
[0141] Comparative Example 2
[0142] The method for preparing the negative electrode active material provided in this comparative example includes the following steps:
[0143] 1. The vacuum stainless steel tube furnace has two vents, allowing for simultaneous gas-driven reactions. 50g of graphite is placed in the vacuum stainless steel tube furnace chamber; silane is introduced into the furnace at a flow rate of 1000ml / min, and the furnace is heat-treated at 500℃ for 6 hours. The silane undergoes thermal decomposition in the 500℃ vacuum tube furnace to form silicon atoms, which are deposited on the pore walls of the porous graphite to form sub-nanometer silicon (<1nm), resulting in an uncoated silicon-carbon composite material.
[0144] 2. Place 50g of uncoated silicon-carbon composite material into a tube furnace again; introduce methane gas into the tube furnace and heat it to 600℃. The methane breaks the CH bond at high temperature and deposits on the surface of the silicon-carbon material particles. Further carbonization at high temperature forms a carbon coating layer, thus obtaining the negative electrode active material.
[0145] Table 1
[0146]
[0147]
[0148] Test case
[0149] 1. Physical property testing
[0150] The negative electrode active materials provided in all embodiments were tested, including the following steps:
[0151] 1) The pore size of the carbon framework was measured using HRTEM;
[0152] 2) The specific surface area of the carbon skeleton was tested using Micromeritics ASAP2046 according to the BET method;
[0153] 3) The degree of graphitization of the carbon framework was tested using Raman spectroscopy;
[0154] 4) The particle size D50 of the negative electrode active material was tested using a laser particle size analyzer according to the wet particle size testing method;
[0155] 5) The mass percentage of each component in the negative electrode active material was tested using nitrogen and sulfur analyzers, EDS, TG and other methods;
[0156] 6) The thickness of the coating layer in the negative electrode active material was tested using HRTEM;
[0157] The specific test results are shown in Table 2.
[0158] Table 2
[0159]
[0160]
[0161] 2. Electrochemical performance testing
[0162] The negative electrode active materials provided in all embodiments and comparative examples are used to prepare coin cells, including the following steps:
[0163] The negative electrode active material, acetylene black, and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 8:1:1 and then coated onto copper foil to obtain the working electrode; a lithium metal sheet is used as the counter electrode; and a PE / PP composite separator is used as the ion exchange membrane to form a coin cell.
[0164] The method for making a button cell battery is as follows:
[0165] 1.1 Prepare materials according to the battery manufacturing method, coat one side, place in a vacuum drying oven for more than 16 hours at a pressure of -0.1MPa and a drying temperature of 85℃, and set aside for use after drying.
[0166] 1.2 After the dried electrode is compacted (without material falling off), use a punching machine to punch out round discs with a diameter of 10mm. Accurately weigh their mass (accurate to 0.01mg) and place them in a weighing bottle. At the same time, accurately weigh the mass of the clean aluminum foil near each electrode to be tested.
[0167] 1.3 Place the weighed electrode sheet to be tested into a vacuum oven at 120℃ and bake for more than 1 hour.
[0168] 1.4 Assembly shall begin when the concentrations of H2O and O2 in the glove box are both below 1 ppm.
[0169] 1.5 After placing various materials into the battery casing in sequence (the order of placement is: positive electrode casing - electrode sheet - separator - lithium metal sheet - gasket - nickel sheet - negative electrode casing), add electrolyte before placing the separator and lithium sheet.
[0170] 1.6 The assembled battery is sealed using a hydraulic sealing machine.
[0171] Charge and discharge performance test: The LANHE battery test system was used to discharge the button cell to 0.005V at a constant current of 0.5A at room temperature, and then charge it to 1.5V at a constant current of 0.5mA. The discharge capacity and charge capacity of the battery were recorded. The initial reversible capacity (mAh / g) = (discharge current × discharge time) / mass of active material. The test results are shown in Table 3.
[0172] Expansion test: Before assembling the coin cell, the original thickness of the electrode sheet of each sample was measured with a micrometer. After 100 cycles using the LANHE battery testing system, the discharge capacity of the battery was recorded. The battery was discharged to 0% SOC, the coin cell was disassembled, the negative electrode sheet was removed, cleaned with DMC solution, and dried before the thickness was tested. The following calculations were made: Capacity retention rate after 100 cycles = (Discharge capacity of the 100th cycle / Initial discharge capacity) × 100%, Electrode sheet expansion rate (%) after 100 cycles = (Thickness after cycles - Original thickness) / Original thickness × 100%. The test results are shown in Table 3.
[0173] Table 3
[0174]
[0175] As shown in Table 3, compared with the comparative example, the negative electrode active material of the embodiment can effectively reduce the expansion rate of the fluorine electrode and improve the cycle stability of the battery under the synergistic effect of the silicon-carbon material with a specific composition and the coating layer.
[0176] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode active material, characterized in that, Includes a silicon-carbon material and a coating layer disposed on at least a portion of the surface of the silicon-carbon material; The silicon-carbon material includes a carbon skeleton, which comprises several carbon nanocages, and the surface of the carbon nanocages is provided with nano-silicon.
2. The negative electrode active material according to claim 1, characterized in that, The carbon skeleton has a pore size of 0.5 nm to 10 nm; And / or, the particle size of the nano-silicon is no greater than 1 nm; And / or, the average size of the carbon nanocages is 8 nm to 30 nm.
3. The negative electrode active material according to claim 1 or 2, characterized in that, The degree of graphitization of the carbon skeleton is 1.6 to 4; And / or, the degree of graphitization of the silicon-carbon material is 1.0 to 2.
8.
4. The negative electrode active material according to any one of claims 1-3, characterized in that, The carbon skeleton is spherical or near-spherical; And / or, the specific surface area of the carbon skeleton is 400–3000 m². 2 / g; And / or, the carbon nanocage is spherical or near-spherical; And / or, the inner surface of the carbon nanocage is provided with the nano-silicon; And / or, the nano-silicon has an amorphous structure.
5. The negative electrode active material according to any one of claims 1-4, characterized in that, The coating layer includes at least one of carbon, metal oxides, phosphate compounds, and aluminate compounds; And / or, the thickness of the coating layer is 5nm-30nm.
6. The negative electrode active material according to any one of claims 1-5, characterized in that, The particle size D50 of the negative electrode active material is 5μm to 15μm.
7. The negative electrode active material according to any one of claims 1-6, characterized in that, Based on the mass of the negative electrode active material, the mass percentage of the nano-silicon is 30%-60%, and the mass percentage of the coating layer is 2%-10%.
8. A method for preparing the negative electrode active material according to any one of claims 1-7, characterized in that, Includes the following steps: 1) The carbon framework precursor was treated at a temperature of 1200℃~3000℃ for 6-14h to obtain a carbon framework including carbon nanocages. 2) The carbon framework is deposited using a silicon source to obtain the silicon-carbon material; 3) A coating layer is formed on the surface of the silicon-carbon material to obtain the negative electrode active material.
9. The preparation method according to claim 8, characterized in that, The carbon framework precursor is a mesophase carbon microsphere; And / or, the temperature of the vapor deposition is 400–600°C, and the time is 4–8 hours.
10. A negative electrode sheet, characterized in that, Includes the negative electrode active material according to any one of claims 1-7 or the negative electrode active material prepared by the preparation method according to claim 8 or 9.
11. A battery, characterized in that, Includes the negative electrode sheet as described in claim 10.
12. A battery pack, characterized in that, It includes at least two batteries as described in claim 11.
13. An electrical appliance, characterized in that, Includes the battery of claim 11 or the battery pack of claim 12.